Performance Measurement of a Compact Generator - Hydro Turbine System - Pudji Irasari; Priyono Sutikno; Puji Widiyanto; Qidun Maulana (International Journal of Electrical and Computer Engineering (IJECE), 2015)
This study aims to investigate the characteristic of a compact generator – hydro turbine system. The generator is of permanent magnet type and the turbine operates in a very low head. The integration of the two components is conducted in such a way that simplifies the construction of the conventional turbine generator. The method is by mounting the generator stator to the turbine casing and the permanent magnets are assembled in the perimeter of the turbine blade rotor. This simple construction is approached by making the stator from individual teeth and yoke. The permanent magnet generator (PMG) is designed to produce the nominal power of 300 Watt 50 Hz at 83 rpm of turbine shaft. All components of the integrated turbine- generator are totally immersed in the water stream. The stator has to be hermitic to avoid water entering the spool. Another issue investigated is the influence of the type of the stator inner casing material to the generator performance. The results show, the PVC material for inner casing has a good influence to the generator performance compared with the mild steel material.